Electric field study of silicon rubber insulator using finite element method (SLIM) - Hamdan, Rohaiza (2006)
Silicone rubber provides an alternative to porcelain and glass regarding to high voltage (HV) insulators and it has been widely used by power utilities since 1980's owing to their superior contaminant performances. Failure of outdoor high voltage (HV) insulator often involves the solid air interface insulation. As result, knowledge of the field distribution around high voltage (HV) insulators is very important to determine the electric field stress occurring on the insulator surface, particularly on the air side of the interface. Thus, concerning to this matter, this project would analyze the electric field distribution of energized silicone rubber high voltage (HV) insulator. For comparative purposes, the analysis is based on two conditions, which are silicon rubber insulators with clean surfaces and silicon rubber insulators with contamination layer taking place over its surfaces. In addition, the effect of water droplets on the insulator surface is also included. The electric field distribution computation is accomplished using SLIM software that performs two dimensions finite element method. The finding from this project shows that pollution layer distort the voltage distribution along the insulator surface while different pollution layer material and variation in zone of incidence would contribute different profile of electric field. Existence of water droplets would create field enhancement at the interface of the water droplet, air and silicon rubber material. Also, the intensification field created by water droplet is depending on the droplets size, number of droplets and the proximity of water droplets to each other.